2002
DOI: 10.1002/ajmg.10133
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic congenital central hypoventilation syndrome: Evaluation of brain‐derived neurotrophic factor genomic DNA sequence variation

Abstract: Idiopathic congenital central hypoventilation syndrome (CCHS) is an unique disorder of respiratory control, occurring in association with Hirschsprung disease (HSCR), tumors of neural crest origin, and symptoms of autonomic nervous system dysfunction (ANSD). CCHS is thought to be genetic in origin based upon 1) affected sib pairs, 2) genetic analysis, and 3) identification of genetic mutations in both HSCR and CCHS patients. Because these mutations have been found in but a few cases of CCHS, exploration of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…In this study, we found the polymorphism T2I (rs8192466) in three unrelated obese individuals (frequency 0.54%). The polymorphism had previously been described in a single extremely obese boy, where the variant had been transmitted by the overweight mother and in a patient with idiopathic congenital central hypoventilation syndrome, where the proband inherited the substitution from his unaffected father and both father and son suffered from oesophageal dysmotility, gastro‐oesophageal reflux and dysphagia . Friedel et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found the polymorphism T2I (rs8192466) in three unrelated obese individuals (frequency 0.54%). The polymorphism had previously been described in a single extremely obese boy, where the variant had been transmitted by the overweight mother and in a patient with idiopathic congenital central hypoventilation syndrome, where the proband inherited the substitution from his unaffected father and both father and son suffered from oesophageal dysmotility, gastro‐oesophageal reflux and dysphagia . Friedel et al .…”
Section: Discussionmentioning
confidence: 99%
“…BDNF acts on neurons of the central and peripheral nervous system (Levi-Montalcini and Calissano, 1979;Leibrock et al, 1989;Purvues et al, 2001); it also rescues many sensory neurons from naturally occurring cell death (Hofer and Barde, 1988) and has been shown to be involved in the regulation of vascular development in ischemic tissues (Donovan et al, 2000;Kermani and Hempstead, 2007). Two main mutations in the BDNF protein are associated with diseases in humans: the most common is V66M, found in association with memory loss and hippocampus hyperactivation (Egan et al, 2003); the other one is L2I, which is associated with the congenital central hypoventilation syndrome, firstly described by Weese-Mayer et al (2002).…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, the allelic variation Thr2Ile (substitution of isoleucine for threonine at aminoacid position 2 in the coding sequence) has been implicated in the congenital central hypoventilation syndrome 23 . The variations in BDNF have been extensively studied and implicated in the susceptibility to memory and hippocampal function impairments 24 , and several psychiatric disorders 25 , such as obsessive-compulsive 26 , eating 27, 28 , bipolar 293034 , schizophrenia 35 , major depression 36, 37 , and Alzheimer’s disease 3840 .…”
Section: Introductionmentioning
confidence: 99%